Badger Vaccination: Dimensions of Trust and Confidence in the Governance of Animal Disease. (December 2014) - Enticott, Gareth; Maye, Damian; Fisher, Rhiannon; Ilbery, Brian; Kirwan, James
This paper examines farmers' trust in badger vaccination as a method of preventing the spread of bovine tuberculosis (bTB) between wildlife (specifically, badgers) and cattle in England. The spread of bTB has economic and social implications for farmers, but previous research has found that lack of trust in government is a key factor in farmers' failure to adopt new preventative biosecurity practices. In these and other studies, however, the conceptual dimensions of trust are frequently loosely defined, meaning that it is unclear how trust, along with other factors, is related to the acceptance of new biosecurity practices such as vaccination. Drawing on findings from a telephone survey of 339 farmers and in-depth interviews with a subsample of 65, the paper explores attitudes towards, and levels of acceptance of, badger vaccination amongst farmers across five study areas with varying levels of bTB disease. Results reveal low levels both of trust in government to manage bTB and confidence in badger vaccination. Principal components analysis identifies three specific dimensions of trust which, along with farmers' perceived self-efficacy, the perceived threat of disease, and faith in others to manage disease, are all significantly related to the acceptability of badger vaccination.